2018
DOI: 10.1111/aor.13118
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Gas Does Not Ameliorate Renal Ischemia Reperfusion Injury in a Preclinical Model

Abstract: In renal transplantation, ischemia reperfusion injury impairs early graft function and can reduce long term graft survival. Hydrogen has antioxidant and anti-inflammatory properties that can reduce the effects of ischemic injury. The aim of this study was to examine the effects of hydrogen gas administered during reperfusion in a preclinical model of kidney ischemia reperfusion injury. Porcine kidneys underwent 15 min of warm ischemia followed by 22 h of cold ischemia. They were then reperfused for 6 h with wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…The determination of has been performed in numerous preclinical and clinical NMP studies, which have focused on therapeutic strategies [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ], the ideal NMP experimental setup [ 42 , 43 , 44 , 45 , 46 , 47 ], or the performance of NMP compared to other preservation methods [ 48 , 49 , 50 ], among others. In these studies, either Fick’s principle (e.g., [ 35 , 42 ]) or the simplified form, the arteriovenous pO 2 difference without consideration of hemoglobin concentration (e.g., [ 37 , 39 ]), served as the basis for calculation.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of has been performed in numerous preclinical and clinical NMP studies, which have focused on therapeutic strategies [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ], the ideal NMP experimental setup [ 42 , 43 , 44 , 45 , 46 , 47 ], or the performance of NMP compared to other preservation methods [ 48 , 49 , 50 ], among others. In these studies, either Fick’s principle (e.g., [ 35 , 42 ]) or the simplified form, the arteriovenous pO 2 difference without consideration of hemoglobin concentration (e.g., [ 37 , 39 ]), served as the basis for calculation.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that both inhalation of hydrogen gas and administration of hydrogen-containing solution contribute equally to eliminate excessive ROS and preserve IR-injured organs . However, hydrogen gas administration showed no significant improvements in renal function and inhibitory effects in inflammation and oxidative damage during reperfusion period, and this potential mechanism remains to be elucidated . Unlike hydrogen, nitric oxide, hydrogen sulfide, and carbon monoxide are endogenous substances and play important roles in cellular signaling transduction and regulation of cell cycle, apoptosis, and oxidative stress .…”
Section: Therapeutic Approaches Against Ir Injurymentioning
confidence: 99%
“…25 However, hydrogen gas administration showed no significant improvements in renal function and inhibitory effects in inflammation and oxidative damage during reperfusion period, and this potential mechanism remains to be elucidated. 26 Unlike hydrogen, nitric oxide, hydrogen sulfide, and carbon monoxide are endogenous substances and play important roles in cellular signaling transduction and regulation of cell cycle, apoptosis, and oxidative stress. 27 Multiple studies demonstrated that restraining endogenous nitric oxide synthase could exacerbate IR injury, indicating that NO has potential in treating IR injury.…”
Section: Therapeutic Approaches Against Ir Injurymentioning
confidence: 99%
“…Sarah A. Hosgood et al of the University of Cambridge, Addenbrookes's Hospital, Cambridge, UK, investigated if hydrogen gas can ameliorate renal ischemia reperfusion injury in a porcine model. Porcine kidneys underwent 15 minutes of warm ischemia followed by 22 hours of cold ischemia.…”
Section: Transplantation and Organ Preservationmentioning
confidence: 99%